Religious Lawyering's Second Wave - Pearce, Russell G. (Journal of law and religion, 2006)
The recent three-hour program on "Professional Responsibility and the Religious Traditions" at the annual meeting of the American Association of Law Schools ("AALS"), sponsored by the Section on Professional Responsibility and co-sponsored by the Section on Law and Religion, represents a milepost in the history of the religious lawyering movement and offers a valuable opportunity to reflect on that history. In 1998, only eight years ago, one of us defined the religious lawyering movement as "an emerging force" in legal ethics. In that short time, the movement has expanded dramatically and has received greater attention within the academy and the bar. It has developed the first institutional vehicles for disseminating and promoting conversations about religious lawyering, both among lawyers of the same faith and among lawyers of different faith traditions. Now the religious lawyering movement is increasingly confronting more complex and more difficult religious, legal and ethical issues; and is extending the religious lawyering conversation internationally.